Writing the Balfour Declaration into the Mandate for Palestine. Issue 2 (4th March 2023) - Pedersen, Susan
Abstract: The Balfour Declaration was an important statement of intent, but it was only one of several wartime statements by British officials about Britain's future plans for Palestine. It was the inclusion of the declaration in the text of the mandate for Palestine that gave this pledge the status of international law and set off two decades of argument over its fulfilment. This article tracks the process by which the declaration came to be included in the mandate text and, more than four years after its issuance, to finally win approval from the Council of the League of Nations. It argues for the crucial role played by Arthur Balfour himself in securing American consent and in overcoming French and Italian reservations.